Better, Sooner, More Convenient? The reality of pursuing greater integration between primary and secondary healthcare providers in New Zealand. (29th March 2017) - Lovelock, Kirsten; Martin, Greg; Gauld, Robin; MacRae, Jayden
Objectives: This article focuses on the results of evaluations of two business plans developed in response to a policy initiative which aimed to achieve greater integration between primary and secondary health providers in New Zealand. We employ the Consolidated Framework for Implementation Research to inform our analysis. The Better, Sooner, More Convenient policy programme involved the development of business plans and, within each business plan, a range of areas of focus and associated work-streams. Methods: The evaluations employed a mixed method multi-level case study design, involving qualitative face-to-face interviews with front-line staff, clinicians and management in two districts, one in the North Island and the other in the South Island, and an analysis of routine data tracked ambulatory sensitive hospitalisations and emergency department presentations. Two postal surveys were conducted, one focussing on the patient care experiences of integration and care co-ordination and the second focussing on the perspectives of health professionals in primary and secondary settings in both districts. Results: Both evaluations revealed non-significant changes in ambulatory sensitive hospitalisations and emergency department presentation rates and slow uneven progress with areas of focus and their associated work-streams. Our evaluations revealed a range of implementation issues, the barriers and facilitators to greater integration of healthcare services and the implications for those who were responsible for putting policy into practice. Conclusion: The business plans were shown to be overly ambitious and compromised by the size and scope of the business plans; dysfunctional governance arrangements and associated accountability issues; organisational inability to implement change quickly with appropriate and timely funding support; an absence of organisational structural change allowing parity with the policy objectives; barriers that were encountered because of inadequate attention to organisational culture; competing additional areas of focus within the same timeframe; and consequent overloading of front-line staff which led to workload stress, fatigue and disillusionment. Where success was achieved, this largely hinged on the enthusiasm of a small pool of front-line workers and their initial buy-into the idea of integrated care.